2022
DOI: 10.1039/d1ew00674f
|View full text |Cite
|
Sign up to set email alerts
|

Formation of halogenated disinfection by-products during ballast water chlorination

Abstract: Halogenated disinfection by-products (DBPs) from ballast water treatment have attracted more attention owing to their potential threats to marine ecosystems. Chlorination is widely used in ballast water treatment, in which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…According to previous studies, the generation of disinfection by-products (DBPs) by sterilization devices using AS is influenced by the form and concentration of oxidants, contact time, organic matter concentration and characteristics, and water quality conditions such as salinity, pH, and temperature [7][8][9][10][11][12]. Shah et al reported that trihalomethanes (THMs) and haloacetic acids (HAAs) are influenced by the degree of salinity (especially the bromide concentration), the concentration and form of the dissolved organic matter (DOM), and the type/dose of oxidants [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, the generation of disinfection by-products (DBPs) by sterilization devices using AS is influenced by the form and concentration of oxidants, contact time, organic matter concentration and characteristics, and water quality conditions such as salinity, pH, and temperature [7][8][9][10][11][12]. Shah et al reported that trihalomethanes (THMs) and haloacetic acids (HAAs) are influenced by the degree of salinity (especially the bromide concentration), the concentration and form of the dissolved organic matter (DOM), and the type/dose of oxidants [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, environmental hazards could increase when ballast water is treated with BWMS using AS in seawater with high bromide concentrations. In addition, the efficiency of BWMS using electrolytic devices is influenced by factors such as the salinity, pH, and water temperature of ship ballast water [3,8,11,17]. Cha et al reported that when the pH drops to around 6, the proportion of HOCl or HOBr increases by about 7%, and these compounds have stronger sterilizing powers than OCland/or OBr - [10].…”
Section: Introductionmentioning
confidence: 99%